Answer :

If three terms are in AP, the difference between the terms should be equal, i.e. if a, b and c are in AP then,
b - a = c - b

Since, the terms are in an AP, therefore

(4k - 6) - (3k - 2) = (k + 2) - (4k - 6)


k - 4 = - 3k + 8


4k = 12


k = 3


k = 3

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Write the first tNCERT - Maths Exemplar

Find the sum of aMathematics - Board Papers

Which of the follNCERT - Maths Exemplar